Retorika Iklan Kampanye Politik Pemilihan Presiden Indonesia 2009 dalam Media Televisi - I Nyoman Larry Julianto; Yasraf Amir Piliang (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
Indonesian presidential election campaign advertisement 2009 in its realization through the medium of television has a wide variety of creative concepts to change the state of mind of the audience target. The creative concept was created to build up the rhetoric to communicate his political message. The main purpose of this research is to know aspects of rhetoric that is used by participants of presidential election 2009 in communicating a political message that reflects the vision and mission through the medium of television political campaign advertisement.Data in the form of political campaign advertisement of presidential election 2009 television media was analyzed by looking directly series of motion picture which has been captured then described with text analysis method in which the overall visual and narrative elements of advertising is a cultural text that became the focus of the study object. To understand aspects of the rhetoric used in political campaign advertisement of each Indonesian presidential election participants 2009, identified with the method of text analysis which is associated with the theory of rhetoric so that will be known the forms of rhetoric and rhetorical strategies used by each presidential candidate and vice presidential candidates in communicating their political message and in it represented an ideology which underlying the combination of signs behind those advertisement. While, understanding the rhetoric of work processes in sign system is identified with the method of text analysis associated with the order of narrative story advertisement. The purpose of understanding of the two main things above is to dissect more critical about aspects of rhetoric, concept of rhetoric and logic rhetoric used in the three advertisements. Critical understanding that is meant here is comparative analysis of rhetorical strategies of each presidential candidate and vice presidential candidates communicating their political messages to build a visual image through a system of signs which is constructed on a political campaign advertisement on television in relation to the concept of rhetoric and logic of rhetoric of each presidential candidate and vice presidential candidates become a rhetorical discourse Indonesian presidential election advertisement 2009 thoroughly through the process of interpretation.